Electrochemical Cycle-Life Characterization of High Energy Lithium-Ion Cells with Thick Li(Ni0.6Mn0.2Co0.2)O2 and Graphite Electrodes. Issue 6 (1st January 2017) - Leng, Yongjun; Ge, Shanhai; Marple, Dan; Yang, Xiao-Guang; Bauer, Christoph; Lamp, Peter; Wang, Chao-Yang
Abstract : A set of high-energy lithium-ion pouch cells consisting of thick Li(Ni0.6 Mn0.2 Co0.2 )O2 (NMC622) cathodes and thick graphite anodes were cycled under 1C-rate charge and 2C-rate discharge at room temperature. Fresh and cycle aged cells were characterized via various techniques, including cell capacity test, in-situ three-electrode cell and electrochemical impedance spectroscopy (EIS). The high-energy cells of ∼200 Wh/kg studied have a cycle life of ∼1419 cycles at capacity retention of ∼75%. It is found that the capacity fade can be characterized into three stages: an initial stage of fast capacity drop, a second stage of gradual capacity loss, and a final stage of sharp capacity fade. The capacity fade is mainly due to loss of lithium inventory in the cells caused by growth of SEI layer during the initial and secondary stages and lithium plating during the final stage. Power fade of the cells is mainly due to the degradation of NMC622 cathode including the growth of surface film on NMC622 electrode active materials and the increase in its charge-transfer resistance. In addition, the power fade exacerbates the cell's capacity fade at low temperatures.